A prodrug strategy for the oral delivery of a poorly soluble HCV NS5B thumb pocket 1 polymerase inhibitor using self-emulsifying drug delivery systems (SEDDS). Issue 2 (15th January 2015) - Beaulieu, Pierre L.; De Marte, Josie; Garneau, Michel; Luo, Laibin; Stammers, Timothy; Telang, Chitra; Wernic, Dominik; Kukolj, George; Duan, Jianmin
Graphical abstract